Black-fly assemblage distribution patterns in streams in disturbed areas in southern Brazil - Couceiro, Sheyla R.M.; Hamada, Neusa; Sagot, Lúcia Beatriz; Pepinelli, Mateus (Acta Tropica, 2014)
Black flies (Simuliidae) are considered to be pests in rural and in some urban areas in the south of Brazil due to the bites of females. Little information exists on the factors that contribute to Simuliidae distribution in these areas. We sampled 39 streams in the state of Rio Grande do Sul in September 2004 to address ecological aspects. Of the 18 species collected, those that occurred in more than 50% of the streams were: Simulium subnigrum Lutz 1910, Simulium pertinax Kollar 1882, Simulium subpallidum Lutz 1910 and Simulium incrustatum Lutz 1910. Species richness was not influenced by any of the environmental or geographical variables considered, and there was no pattern of species co-occurrence, corroborating the hypothesis of a stochastic distribution of the Simuliidae assemblage. When analyzed individually, only three of seven species with occurrence frequency >30% were related to any of the variables measured. The probabilities of occurrence of Simulium jujuyense Paterson & Shannon 1927 and S. pertinax were higher in streams with high values of water pH and electrical conductivity, whereas the opposite was observed for S. incrustatum. Therefore, due to stochastic distribution, the population studies of Simuliidae are more suitable for predicting the occurrence of species in rural areas than are studies of assemblages. © 2014 Elsevier B.V.
Keywords: Aquatic Ecosystem; Environmental Disturbance; Fly; Neotropical Region; Population Distribution; Rural Area; Spatial Distribution; Species Occurrence; Stochasticity; Stream; Assembly Rule; Geographical Distribution; Pest Species; Species Richness; Streamwater; Altitude; Aquatic Environment; Electric Conductivity; Geography; Insect; Larva; Neotropics; Nonhuman; Ph; Rural Area; Simuliidae; Simulium; Simulium Clavibranchium; Simulium Incrustatum; Simulium Jujuyense; Simulium Minusculum; Simulium Perflavum; Simulium Pertinax; Simulium Rubrithorax; Simulium Spinibranchium; Simulium Subnigrum; Simulium Subpallidum; Simulium Tnaequale; Simulium Tncrustatum; Species Distribution; Species Identification; Species Richness; Stream (river); Vegetation; Water Temperature; Controlled Study; Environmental Factor; Simulium Incrustatum; Species Coexistence; Animals; Classification; Female; Insect Bites And Stings; Insect Control; Microbiology; River; Simuliidae; Rio Grande Do Sul; Water; Simuliidae; Simulium Nigricoxum; Animal; Female; Insect Bites And Stings; Insect Control; Rivers; Simuliidae; Water Microbiology